2016
DOI: 10.1063/1.4953370
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast electron crystallography of the cooperative reaction path in vanadium dioxide

Abstract: Time-resolved electron diffraction with atomic-scale spatial and temporal resolution was used to unravel the transformation pathway in the photoinduced structural phase transition of vanadium dioxide. Results from bulk crystals and single-crystalline thin-films reveal a common, stepwise mechanism: First, there is a femtosecond V−V bond dilation within 300 fs, second, an intracell adjustment in picoseconds and, third, a nanoscale shear motion within tens of picoseconds. Experiments at different ambient temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…S5 ). Such multi-stage diffraction evolution is qualitatively consistent with the earlier UED studies 34 , 35 , 37 , 38 , although we will point out the distinct differences found here in a strained ultrathin specimen.
Figure 4 Time-resolved diffraction changes and intracell motions of vanadium ions.
…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…S5 ). Such multi-stage diffraction evolution is qualitatively consistent with the earlier UED studies 34 , 35 , 37 , 38 , although we will point out the distinct differences found here in a strained ultrathin specimen.
Figure 4 Time-resolved diffraction changes and intracell motions of vanadium ions.
…”
Section: Resultssupporting
confidence: 91%
“…3c , blue). Moreover, no long-term lattice expansion is seen at F ex < 5 mJ/cm 2 , whose excitation threshold behavior coincides with those reported in previous time-resolved studies 26 29 , 34 , 35 , 37 , 38 . These results, as well as the long-time dynamics discussed below, suggest that the photoinjected energy is redistributed among multiple components of the structural dynamics, including the overshooting and then reduced amount of strain release as well as the intracell ionic motions along different directions (see below).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As shown in numerous works, 22,[38][39][40][41][42][43][44][45] the photoinduced IMT in VO 2 depends on incident light intensity, wavelength, and also on film crystallinity, structural defects, and internal strain. Recent studies indicate that the ultrafast structural phase transition (SPT) is likely to be triggered by a screening of electron correlations on the sub-picosecond scale.…”
Section: Introductionmentioning
confidence: 88%